Analysis of the factors affecting the demand for Algerian insurance companies products: A study on a sample of insurance companies - Hamza, Bachiri; Amara, Abdelkader; Toufik, Ghafsi (The International tax journal, 2025)
Because it plays a major role in protecting other financial sectors and the nation's economy overall, the insurance sector is crucial to the economic framework. Due in large part to the issuance of Order No. 07-95 and the amendment to Law No. 06-04 of February 24, 2006, Algeria's insurance industry has been a focus of state attention since independence and has seen notable developments in line with both national economic policies and global trends toward the liberalization of trade in financial services. This study determined the economic variables—such as GDP, unemployment, and inflation that affect the demand for insurance products in the Algerian market. The findings show that these elements significantly influence Algeria's rising demand for insurance goods. The survey also found that the largest portion of the Algerian insurance market is made up of property insurance, especially auto insurance.